Data_Sheet_1_Immobilized Lipase in the Synthesis of High Purity Medium Chain Diacylglycerols Using a Bubble Column Reactor: Characterization and Application.pdf - Jiazi Chen; Wan Jun Lee; Chaoying Qiu; Shaolin Wang; Guanghui Li; Yong Wang (2020)
Novozym ® 435, an immobilized lipase from Candida antarctica B. (CALB), was used as a biocatalyst for the synthesis of high purity medium chain diacylglycerol (MCD) in a bubble column reactor. In this work, the properties of the MCD produced were characterized followed by determining its practical application as an emulsifier in water-in-oil (W/O) emulsion. Two types of MCDs, namely, dicaprylin (C 8 -DAG) and dicaprin (C 10 -DAG), were prepared through enzymatic esterification using the following conditions: 5% Novozym ® 435, 2.5% deionized water, 60°C for 30 min followed by purification. A single-step molecular distillation (MD) (100–140°C, 0.1 Pa, 300 rpm) was performed and comparison was made to that of a double-step purification with MD followed by silica gel column chromatography technique (MD + SGCC). Crude C 8 -DAG and C 10 -DAG with DAG concentration of 41 and 44%, respectively, were obtained via the immobilized enzyme catalyzing reaction. Post-purification via MD, the concentrations of C 8 -DAG and C 10 -DAG were increased to 80 and 83%, respectively. Both MCDs had purity of 99% after the MD + SGCC purification step. Although Novozym ® 435 is a non-specific lipase, higher ratios of 1,3-DAG to 1,2-DAG were acquired. Via MD, the ratios of 1,3-DAG to 1,2-DAG in C 8 -DAG and C 10 -DAG were 5.8:1 and 7.3:1, respectively. MCDs that were purified using MD + SGCC were found to contain 1,3-DAG to 1,2-DAG ratios of 8.8:1 and 9.8:1 in C 8 -DAG and C 10 -DAG, respectively. The crystallization and melting peaks were shifted to higher temperature regions as the purity of the MCD was increased. Dense needle-like crystals were observed in MCDs with high purities. Addition of 5% C 8 -DAG and C 10 -DAG as emulsifier together in the presence of 9% of hydrogenated soybean oil produced stable W/O emulsion with particle size of 18 and 10 μm, respectively.